Pergerakan dan Pencucian Hara pada Tanah Typic Hapludult di Taman Nasional Bukit Duabelas: Hubungan Kation-anion - Putra, Gilang Sukma; Hartono, Arief; Anwar, Syaiful; Murtilaksono, Kukuh (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Soil Nutrient are dynamics. Their amount and movement within soil solution can determine its fertility to accomodate plant growth. The dissolved nutrients are moving together in the form of cations and anions. This study aims to determine the amount of dissolved cation-anion in the soil solution and to evaluate its relationship. Field trial was conducted at tropical rainforest of Bukit Duabelas National Park. The Lisymeter was installed on each Typic Hapludult soil horizon to accommodate percolated water. The leached water sample was extracted and each cation (NH4+, Ca2+, Mg2+, K+) and anion (PO43-, Cl-, SO42-, NO3-) concentration were measured. Data were analyzed using independent-t stastical test, Spearman correlation, and stepwise linear regression. The results show that the total amount of cation and anion are significantly higher in the AO horizon than the AB and B horizons. The correlation analysis results show that each cation has a strong correlation to each anion (correlation value > 0.80) except PO43- ( ~ 0.70). Stepwise linear regression model shows that NH4+ has the strongest relation to NO3-, PO43-, and Cl- with R2 adj.= 0.75, Ca2+ to NO3-, PO43-, and SO42- (R2 adj.= 0.856), Mg2+ to NO3- and  PO43- (R2 adj.= 0.815), and K+ to PO43- and Cl-  (R2 adj.= 0.845). It can be concluded that NO3-, Cl-, SO42-, and PO43- are directly involved as cation co-pairing agents in the soil nutrient movement and leaching process.